THE EFFECTS OF BUDGET MANAGEMENT AND FINANCIAL TRANSPARENCY TOWARD THE EFFECTIVENESS OF FUND UTILIZATION THROUGH THE FINANCIAL ACCOUNTABILITY AT THE DEPARTMENT MINISTRY OF RELIGIOUS AFFAIRS IN MAMUJU REGENCY - Yusuf, Aco M.; Anshar, Muh. Ashary; Syam, Andi Faisal (Yayasan Education and Social Center, 2025)
This study aims to find the latest model by elaborating on financial accountability in mediating budget management, and financial transparency towards the effectiveness of fund use at the Ministry of Religious Affairs Office of Mamuju Regency. This study was conducted at the Ministry of Religious Affairs Office of Mamuju Regency, lasting for approximately 2 (two) months, namely May 2025 to June 2025. The population in this study were all ASN at the Ministry of Religious Affairs Office of Mamuju Regency, totaling 101 ASN. Data collection techniques were carried out through observation, questionnaires and documentation, while data analysis usedStructural Equation Modeling with Partial Least Squares(PLS-SEM). The results of the study show that: (1) Budget management directly has a positive and significant effect on financial accountability at the Office of the Ministry of Religion of Mamuju Regency, (2) Financial transparency directly has a positive and significant effect on financial accountability at the Office of the Ministry of Religion of Mamuju Regency, (3) Budget management directly has a positive and significant effect on the effectiveness of the use of funds at the Office of the Ministry of Religion of Mamuju Regency, (4) Financial transparency directly has a positive and significant effect on the effectiveness of the use of funds at the Office of the Ministry of Religion of Mamuju Regency, (5) Financial accountability has a positive and significant effect on the effectiveness of the use of funds at the Office of the Ministry of Religion of Mamuju Regency, (6) Budget management directly has a positive and significant effect on the effectiveness of the use of funds through financial accountability at the Office of the Ministry of Religion of Mamuju Regency, (7) Financial transparency directly has a positive and significant effect on the effectiveness of the use of funds through financial accountability at the Office of the Ministry of Religion of Mamuju Regency.